ANALISIS RESEPSI PESAN TOLERANSI LGBT DALAM KELUARGA PADA FILM DOKUMENTER “ALL IN MY FAMILY” (Universitas Negeri Surabaya, 2023)
This research was conducted to find out how the audience perceives the issue of acceptance and toleranceof the LGBT community in a family. Especially those who are with Asian culture, as what shown in Netflixdocumentary film “All in My Family”. Among Indonesian people who understood the concept of a family,tolerance, and also the LGBT community, it was found that none of them were in a position against(Opposition), but instead they supported (Dominant Hegemony) and also negotiated (Negotiation) thecontents of the message of tolerance in the film with the reality and understanding they have. The informantsagreed that, in families especially those with traditions or conservative mindsets such as Asian societies,there is still a need for strong affection and a sense of attachment, good relations, and open communicationamong families to be able to support the survival of its members, including those in LGBTQ+ community.Even though basically the right to freedom of expression and mutual acceptance must exist, in a social orderthat has regulatory norms, this cannot be done selfishly or only one party is concerned.